Towards an evolving Philippine variety of English - Casambre, Nelia G.
This research will look into the phonological, lexico-semantic, and syntactic features of this English variety as reflected in some Philippine mass media. Two TV programs Tell the People and Viewpoint were the selected sources of data for the oral phase, henceforth to be called the spoken word in this study.
Keywords: Mass media and language; English language -- Philippines